ETHANOLIC EXTRACTS OF HEDYOTIS CORYMBOSA L. IMPROVES MONOSODIUM IODOACETATE-INDUCE OSTEOARTHRITIS IN RAT - Bahtiar, Anton; Sari, Fitri Arum; Mega Audina; Datunsolang, Natasha Linsie Corona; Arsianti, Ade (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The objective of this study is to explore the effects of the 70% ethanolic extract of pearl grass on the immune system of the osteoarthritis model rat, characterized by the number of leukocytes and lymphocytes, and the histology of the joint. Osteoarthritis is a degenerative disease characterized by chronic inflammation in the joints. Based on the daily practice of herbal medicine in some community in Indonesia, pearl grass usually used for anti-inflammation but not a lot of data to support it. Methods: We used 36 male rats Sprague-Dawley strain divided into 6 groups. Normal group was given 0.5% of CMC, the negative control group was given 0.025 ml of sodium iodoacetate in 0.9% saline, the positive groups control group was given a suspension of glucosamine-chondroitin 135 mg/200 g bb, three were given pearls grass extract in various dose 5.625 mg, 11.25 mg, and 22.5 mg, respectively. 28 days after sodium iodoacetate induction, the extracts were given orally once daily for 21 days. Measurement of inflammation of knee joint and the number of leukocytes and lymphocytes were counted on day 14th, 28th, and 49th after sodium iodoacetate induction. After treatment, all rats were sacrified and all knee joints were collected to subject for histology. Results: The results showed that the extract of pearl grass in all doses was able to decrease the number of leukocytes and lymphocytes significantly and prevent proteoglycan degradation. The results showed that the extract of pearl grass with a given dose variations have antiinflammation effect and been able to protect proteoglycan significantly. Conclusion: Doses 3 (22.5 mg/200 g BW) is the best result. These results indicate that pearl grass can be further investigated as a treatment for osteoarthritis. Keyword: Osteoarthritis, Sodium iodoacetate, Pearl grass, Hedyotis corymbosa L. Lamk., Immune system. Â